2008
DOI: 10.1162/jocn.2008.20006
|View full text |Cite
|
Sign up to set email alerts
|

Neural and Behavioral Evidence for Affective Priming from Unconsciously Perceived Emotional Facial Expressions and the Influence of Trait Anxiety

Abstract: Abstract& Affective judgments can often be influenced by emotional information people unconsciously perceive, but the neural mechanisms responsible for these effects and how they are modulated by individual differences in sensitivity to threat are unclear. Here we studied subliminal affective priming by recording brain potentials to surprise faces preceded by 30-msec happy or fearful prime faces. Participants showed valenceconsistent changes in affective ratings of surprise faces, although they reported no kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
98
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 85 publications
12
98
1
2
Order By: Relevance
“…In this subgroup stronger tinnitus-severity complaints are accompanied by stronger affective priming of threat-related information and weaker affective priming for positive affective information and these relations became stronger after controlling for hearing loss at normal and high frequency levels. This result is in line with the study of Li et al [15], who found especially stronger affective priming driven by threatening stimuli for subjects with high trait anxiety as compared to those with low trait anxiety. Furthermore, we found normal priming effects and not reversed ones, which is in line with former research findings [14] where affective priming was found in people with high trait anxiety, and reversed priming effects in people with low trait anxiety.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this subgroup stronger tinnitus-severity complaints are accompanied by stronger affective priming of threat-related information and weaker affective priming for positive affective information and these relations became stronger after controlling for hearing loss at normal and high frequency levels. This result is in line with the study of Li et al [15], who found especially stronger affective priming driven by threatening stimuli for subjects with high trait anxiety as compared to those with low trait anxiety. Furthermore, we found normal priming effects and not reversed ones, which is in line with former research findings [14] where affective priming was found in people with high trait anxiety, and reversed priming effects in people with low trait anxiety.…”
Section: Discussionsupporting
confidence: 93%
“…Anxious people are typically described as constantly scanning the environment for possible threats [16,17,20]. In terms of the affective priming task, such a threat-related bias may imply that anxious subjects are faster in deciding that a threatening stimulus is unpleasant [15], which is in line with network theory of mood and memory [12,21].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…These findings of subliminal priming not only were surprising in their own right, but also influenced theories of human information processing (see, e.g., Greenwald, Abrams, , emotional processing (see, e.g., Li, Zinbarg, Boehm, & Paller, 2008), and mental pathology (see, e.g., Dehaene et al, 2003). Although the claim of subliminal priming is influential, the demonstrations of its existence have been critiqued on statistical grounds (Dosher, 1998;Reingold & Merikle, 1988;Rouder, Morey, Speckman, & Pratte, 2007).…”
mentioning
confidence: 86%
“…A second possible expla-P1 effects, however, were not modified by trait anxiety. There are relatively few studies examining links between anxiety and ERP responses to expressive faces, but, of those conducted, effects of anxiety on early sensory components such as the P1 have been reported by some groups (e.g., Holmes et al, 2008;Li, Zinbarg, Boehm, & Paller, 2008) but not others (e.g., Bar-Haim, Lamy, & Glickman, 2005). Further work is needed to examine the influence of anxiety on posterior components triggered by emotional expressions.…”
Section: Lpp At Frontocentral Locations (Late Phase: Poststimulus Meamentioning
confidence: 99%